2020
DOI: 10.1371/journal.pone.0224588
|View full text |Cite
|
Sign up to set email alerts
|

Optimal fertigation for high yield and fruit quality of greenhouse strawberry

Abstract: Nitrogen (N), phosphorus (P), potassium (K), and water are four crucial factors that have significant effects on strawberry yield and fruit quality. We used a 11 that involved 36 treatments with five levels of each of the four variables (N, P, and K fertilizers and water) to optimize fertilization and water combination for high yield and quality. Moreover, we used the SSC/TA ratio (the ratio of soluble solid content to titratable acid) as index of quality. Results showed that N fertilizer was the most importan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Availability of nitrogen is the most important factor for its production and fruit quality [12]. In effect, vegetables and fruit produced with sufficient availability of nutrients contain a high level of total phenols, flavonoids, organic acids, sugars, and L -ascorbic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…Availability of nitrogen is the most important factor for its production and fruit quality [12]. In effect, vegetables and fruit produced with sufficient availability of nutrients contain a high level of total phenols, flavonoids, organic acids, sugars, and L -ascorbic acid [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicated that organically produced fruits and vegetables contain higher levels of flavonoids, anthocyanins, total phenolic compounds, sugars, organic acids, and L-ascorbic acid [12][13][14][15][16]. The increased concern of the consumers about the negative effects of agro-chemicals, driven an upward trend in organic production [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the major factors that has been continuously investigated through different studies is the water content and its effects on the yield and strawberry quality [ 4 , 5 ]. Strawberry cultivars have different demands of water content and fertilization to reach acceptable levels of both quality and yield [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. Previous literature reports that a water deficit has a drastic effect on the strawberry yield and marketability (size of the fruit) on most strawberry cultivates [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the overuse or wrong kind of fertilization can harm the strawberry size and sweetness [ 8 , 13 ]. Wu et al [ 10 ] studied the effect of four different factors (nitrogen (N), phosphorus (P), potassium (K), and water) on the yield and the strawberry sweetness ratio (SSC/TTA), where they found a significant effect on the yield and SSC when they applied the N fertilizer. While the water content had a significant effect on yield, P fertilizers had a significant effect on the sweetness ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation